A INDIKASI AGRESIVITAS PAJAK PADA PERUSAHAAN SEKTOR ENERGI DI BURSA EFEK INDONESIA (BEI) TAHUN 2019-2023 - Khayati, Putri Aisah; Minarso, Bambang; Susilowati Mardjono, Enny; Setiawanta, Yulita (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
The purpose of this study is to investigate the relationship between tax aggression and variables such as capital intensity, inventory intensity, and leverage. The mining companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023 are the focus of this research. The used sample approach is purposive sampling. The research sample comprises 21 businesses operating in the energy industry, with a total of 105 observations. The statistical method used to examine the hypotheses is multiple regression using SPSS version 20. The findings indicate that the level of capital investment and financial leverage does not influence the degree of tax aggressiveness. However, the level of inventory investment does have a significant effect on tax aggressiveness.